VLADIMIR BESLEAGA’S DREAM JOURNAL (MANUSCRIPT): INTROSPECTIVE VIEWS ON OUR OWN EXISTENCE - Nadejda IVANOV (Academy of Sciences of Moldova, 2021)
The article analyzes Vladimir Besleaga’s dream diary, an original manuscript, unknown to the wide public, which can be consulted at the National Museum of Romanian Literature “Mihail Kogalniceanu”, the collection of “Manuscripts”. The manuscript was offered by the author to the researcher, PhD in philology Ana Ghilas and the undersigned, in order to explore the depths of the creative imaginary of the nonagenarian Bessarabian writer. Thus, in the diary we will recognize some recurring images impregnated in the literary creation of Vladimir Besleaga – village, house, mother, water, father etc. The usual area and childhood experiences are for the author of this diary (with the title of manuscript Dreams of night and day (diary ante- anti- octogenate)) an endless source of miracles that helps him to renew his creative impulses and to put in order his ordinary, profane human condition with sacred elements from the abyss of being.